T cells expressing gamma delta chain receptors in rheumatoid arthritis. - Brennan, F; Londei, M; Jackson, A; Hercend, T; Brenner, M; Maini, R; Feldmann, M (1988)
Whereas the majority of T cells use alpha and beta chains to form their T-cell receptor, a small minority of T cells, which do not express the CD4 or CD8 surface markers, use other chains termed gamma and delta to form their receptor. Flow cytometry was performed on cells isolated from the blood and synovial joints of patients with rheumatoid arthritis. Monoclonals which recognise the gamma and delta chains were used to compare the proportion of TCR gamma delta cells in these sites. Approximately half the patients had more TCR gamma delta in the joints than in their blood and one newly diagnosed patient had high numbers of TCR gamma delta cells in both blood and joints. In this preliminary study it is not possible to evaluate the role of these cells in the disease process, but it is of interest that in some RA patients there is an overabundance of both T cells that arise early in ontogeny (TCR gamma delta cells) and B cells that arise early in ontogeny, the CD5 B cell.